Design of optimal transfers between North and South Pole-sitter orbits - Heiligers, Jeannette; Ceriotti, Matteo; McInnes, Colin; Biggs, James (2012)
Recent studies have shown the feasibility of an Earth pole-sitter mission, where a spacecraft follows the Earth’s polar axis to have a continuous, hemispherical view of one of the Earth’s Poles. However, due to the tilt of the polar axis, the North and South Poles are alternately situated in darkness for long periods dur-ing the year. This significantly constrains observations and decreases mission scientific return. This paper therefore investigates transfers between north and south pole-sitter orbits before the start of the Arctic and Antarctic winters to maximize scientific return by observing the polar regions only when lit. Clearly, such a transfer can also be employed for the sole purpose of visiting both the North and South Poles with one single spacecraft during one single mission. To enable such a novel transfer, two types of propulsion are proposed, including so-lar electric propulsion (SEP) and a hybridization of SEP with solar sailing. A di-rect optimization method based on pseudospectral transcription is used to find both transfers that minimize the SEP propellant consumption and transfers that trade-off SEP propellant consumption and observation time of the Poles. Also, a feedback control is developed to account for non-ideal properties of the solar sail. It is shown that, for all cases considered, hybrid low-thrust propulsion out-performs the pure SEP case, while enabling a transfer that would not be feasible with current solar sail technology.